Impact of team diversity and conflict on project performance in Indonesian start-ups - Budi Hartono; Luthfi Dzulfikar; Retno Damayanti (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: Grounded to social identity and information decision theories, the study develops and empirically verifies a fresh theoretical model on the possible mediating effect of emotional and task conflicts toward the associations between diversity (work, social, and ideology) and project performance. Design/methodology/approach: A survey was performed, and 68 Indonesian start-ups provided positive responses accounting for a 57.6% response rate. In total, 102 Indonesian project teams participated, and since multiple team members were inquired for respective teams, 395 individual respondents were involved. An aggregation protocol was utilized to compute team-level datasets. The partial least square (PLS) method was utilized for the main analysis. Findings: The findings suggest a detrimental effect of heightened ideology polarization towards team performance as mediated by emotional conflict. Moreover, work diversity positively affects task conflict, but it does not positively affect team performance. Possible moderating variables such as cultural aspects may lessen the impact. Research limitations/implications: The study offers an updated theoretical model which pertains to diversity, conflict and performance. It also offers unique empirical evidence to examine the theoretical propositions within the setting of Indonesian start-ups. The sample size is rather limited even though it is substantially larger than similar past studies. This could result in a relatively low statistical power. Practical implications: It offers useful practical insights for start-ups to improve their project performance by looking at the intricate association between aspects of team diversity, conflict, and project success. Originality/value: This study extends the contemporary knowledge on diversity studies, by focusing on the project context of Indonesian start-ups.
Keywords: 650; Diversity; conflict; team performance; project team effectiveness; developing countries